DESIGN AND EVALUATION OF CHRONOTHERAPEUTIC PULSATILE DRUG DELIVERY SYSTEM OF CILNIDIPINE - C, Nweje-Anyalowu Paul; A, Anyalogbu Ernest A; Jim, White Alalibo (Universal Journal of Pharmaceutical Research, 2017)
Objectives: Cilnidipine is the novel calcium antagonist accompanied with L-type and N-type calcium channel blocking function used for the treatment of hypertension. The aim of present work is formulate and evaluate a press coated pulsatile release tablets of Cilnidipine using an admixture of hydrophilic polymers in order to achieve a predetermined lag time for chronopharmacotherapy of Hypertension. Methods: The pulsatile drug release tablets were prepared by compression coating method. The tablets prepared were evaluated for different properties like bulk density, tapped density, angle of repose and Carr’s index), hardness, thickness, weight variation, friability, drug content uniformity and in vitro drug release study. Results: All formulations have shown good flow properties. The hardness of tablets ranged between 4.93±0.08 to 5.96±0.11 kg/cm2, percentage friability of tablets ranged between 0.68±0.21 to 0.82±0.06. Maximum drug release was found to be 94.39%. Conclusion: Study concludes that the prepared pulsatile drug delivery system can be considered as one of the promising formulation technique for delivery of Cilnidipine. Formulation of batch CPT1was found to be optimum. Peer Review History: Received 15 August 2017; Revised 13 September; Accepted 28 October; Available online 15 November 2017 Academic Editor: Ahmad Najib , Universitas Muslim Indonesia, Indonesia, ahmad.najib@umi.ac.id Reviewer(s) detail: Dr. Viney Chawla , University Institute of Pharmaceutical Sciences, Baba Farid University of Health Sciences, Sadiq Road, Faridkot-Punjab 151203, drvineychawla@gmail.com Dr. Barkat Ali Khan , Kampala International University , Uganda, barki.gold@gmail.com